2018
DOI: 10.1002/adtp.201800008
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Responsive PEGylated Gold Nanorod and Doxorubicin Loaded Dissolvable Hyaluronic Acid Microneedles for Human Epidermoid Cancer Therapy

Abstract: Currently, epidermoid cancer is one of the most common malignancies among Caucasians. Traditional treatment may yield uncomfortable side effects for the patient. In order to solve these problems, the authors develop a near-infrared (NIR) responsive PEGylated gold nanorod (GNR-PEG) and doxorubicin (DOX) loaded dissolvable hyaluronic acid (HA) microneedle (GNR-PEG&DOX@HA MN) for human epidermoid cancer therapy. The as-made GNR-PEG&DOX@HA MNs has good skin penetration capability and heating ability. The heating c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 63 publications
1
22
0
Order By: Relevance
“…In Vitro Cytotoxicity Assay: The cell cytotoxicity assay was investigated using the MTT method. [20] In short, a density of 4 × 10 3 CT26 cells was seeded into a 96-well plate for 24 h. CPT, HPPH, CPT-CC-HPPH NP, CPT-CC-HPPH/Pt NP, CPT-TK-HPPH NP, and CPT-TK-HPPH/Pt NP with various concentrations were added and cultured for 12 h. The cells were treated with or without 660 nm laser irradiation at 200 mW cm −2 for 5 min as designed. The cells were then incubated for 12 and 36 h following the standard MTT method.…”
Section: Methodsmentioning
confidence: 99%
“…In Vitro Cytotoxicity Assay: The cell cytotoxicity assay was investigated using the MTT method. [20] In short, a density of 4 × 10 3 CT26 cells was seeded into a 96-well plate for 24 h. CPT, HPPH, CPT-CC-HPPH NP, CPT-CC-HPPH/Pt NP, CPT-TK-HPPH NP, and CPT-TK-HPPH/Pt NP with various concentrations were added and cultured for 12 h. The cells were treated with or without 660 nm laser irradiation at 200 mW cm −2 for 5 min as designed. The cells were then incubated for 12 and 36 h following the standard MTT method.…”
Section: Methodsmentioning
confidence: 99%
“…However, finding an administration route for co-delivery has remained a big challenge that can be addressed by MNs. For this purpose, DOX-encapsulated dissolvable hyaluronic acid MNs (DOX-loaded HA MNs) containing a PEGylated gold nanorod (PEGylated-GNR) as a NIR light-responsive agent was developed for human epidermoid cancer therapy [ 131 ]. In this system, PEGylated-GNR acted as a photothermal agent, and hyaluronic MNs presented a high DOX loading capacity and good skin penetration capability.…”
Section: Potential Applications Of Mn Combination With Npsmentioning
confidence: 99%
“…Also anticancer drugs belong to an important field of application of MNDs: two research groups have investigated on DOX administration by means of MNs in [44] and in [45]. Nguyen et al found in vitro studies that Polyvinyl Alcohol (PVA) MNs enhance the transdermal delivery of DOX.…”
Section: Drug Delivery Patchesmentioning
confidence: 99%